The association between the CD4/CD8 ratio and surgical site infection risk among HIV-positive adults: insights from a China hospital - Liu, Bo; Li, Kangpeng; Li, Shengtao; Zhao, Rugang; Zhang, Qiang (Frontiers in Immunology, 2023)
Abstract Purpose: It is well known that the CD4/CD8 ratio is a special immune-inflammation marker. We aimed to explore the relationship between the CD4/CD8 ratio and the risk of surgical site infections (SSI) among human immunodeficiency virus (HIV)-positive adults undergoing orthopedic surgery. Methods: We collected and analyzed data from 216 HIV-positive patients diagnosed with fractures at the department of orthopedics, Beijing Ditan Hospital between 2011 and 2019. The demographic, surgical, and hematological datas for all patients were collected in this retrospective cohort study. We explored the risk factors for SSI using univariate and multivariate logistic regression analysis. Then, the clinical correlation between the CD4 count, CD4/CD8 ratio, and SSI was studied using multivariate logistic regression models after adjusting for potential confounders. Furthermore, the association between the CD4/CD8 ratio and SSI was evaluated on a continuous scale with restricted cubic spline (RCS) curves based on logistic regression models. Results: A total of 23 (10.65%) patients developed SSI during the perioperative period. Patients with hepatopathy (OR=6.10, 95%CI=1.46-28.9), HIV viral load (OR=8.68, 95%CI=1.42-70.2; OR=19.4, 95%CI=3.09-179), operation time (OR=7.84, 95%CI=1.35-77.9), and CD4 count (OR=0.05, 95%CI=0.01-0.23) were risk factors for SSI (P-value < 0.05). Our study demonstrated that a linear relationship between CD4 count and surgical site infection risk. In other words, patients with lower CD4 counts had a higher risk of developing SSI. Furthermore, the relationship between CD4/CD8 ratio and SSI risk was non-linear, inverse 'S' shaped. The risk of SSI increased substantially when the ratio was below 0.913; above 0.913, the risk of SSI was almost unchanged. And there is a 'threshold-saturation' effect between them. Conclusion: Our research shows the CD4/CD8 ratio could be a useful predictor and immune-inflammation marker of the risk of SSI in HIV-positive fracture patients. These results, from a Chinese hospital, support the beneficial role of immune reconstitution in HIV-positive patients prior to orthopedic surgery.